Natural circulation flow distribution within a multi-branch manifold. (June 2019) - Quintanar, Nicolas R.; Nguyen, Thien; Vaghetto, Rodolfo; Hassan, Yassin A.
Highlights: Study of natural circulation flow characteristics within a multi-branch manifold. PIV measurements were performed in the main channel and 9 outlets. Flow statistics were analyzed and compared between various sections of the manifold. Flow in outlets behave similarly, while the main channel has a back-flow region. Experimental results can be used for validating system and CFD codes. Abstract: Natural circulation systems are extensively used in different applications but they need to be fully characterized to understand their behavior under different boundary conditions. CFD tools provide means to analyze these systems, however, they need additional experimental data to be validated. Experimental measurements of the flow distribution within a multiple-branch manifold under natural circulation have been conducted using PIV. Measurements have demonstrated that the flow within the risers behave similarly, differing between 6.68% and 12.63% in speed and vertical velocity, and between 8.7% and 17.5% for vertical turbulence strength at selected heights. A back-flow region has been observed at the bottom of the main channel, with an increasing cross sectional area moving far from the manifold inlet, while stream-wise flow occupies the top section of the main channel. The experimental activity has also produced a complete experimental data set with first and second order statistics of the flow that can be used for CFD code validation.